Observation of Higgs boson production in association with a top quark pair at the LHC with the ATLAS detector - Alconada Verzini, María Josefina (2018)
The observation of Higgs boson production in association with a top quark pair (t¯tH), based on the analysis of proton–proton collision data at a centre-of-mass energy of 13TeVrecorded with the ATLAS detector at the Large Hadron Collider, is presented. Using data corresponding to integrated luminosities of up to 79.8fb−1, and considering Higgs boson decays into b¯ b, WW∗, τ+τ−, γγ, and ZZ∗, the observed significance is 5.8 standard deviations, compared to an expectation of 4.9 standard deviations. Combined with the t¯tHsearches using a dataset corresponding to integrated luminosities of 4.5fb−1at 7TeVand 20.3fb−1at 8TeV, the observed (expected) significance is 6.3 (5.1) standard deviations. Assuming Standard Model branching fractions, the total t¯tHproduction cross section at 13TeVis measured to be 670±90(stat.)+110−100(syst.)fb, in agreement with the Standard Model prediction.